2012
DOI: 10.1016/j.jtcvs.2011.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of pericardial leaflet structure from balloon-expanded valved stents

Abstract: Analysis of valved stent expansion showed a displacement of the stent on the catheter during balloon inflation. Therefore, precise placement of the valved stent cannot be accomplished. Histologic analysis of the expanded pericardial tissue revealed disruption of collagen fibers. Disruption of pericardial tissue structures due to balloon expansion may result in early functional valve failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 14 publications
(12 reference statements)
1
21
0
1
Order By: Relevance
“…Because of the nature of the preparation process and the potential for increased crimping time, it was important to evaluate the detrimental effects this process would have on the tissue leaflets [15]. For instance, de Buhr and colleagues [7] studied the effect of balloon expansion on leaflet structure. They observed disruption of collagen fibers in pericardial tissues, confirmed by purely qualitative histology [16].…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the nature of the preparation process and the potential for increased crimping time, it was important to evaluate the detrimental effects this process would have on the tissue leaflets [15]. For instance, de Buhr and colleagues [7] studied the effect of balloon expansion on leaflet structure. They observed disruption of collagen fibers in pericardial tissues, confirmed by purely qualitative histology [16].…”
Section: Commentmentioning
confidence: 99%
“…Microdisturbances in right-side heart valves owing to particulate matter lead to an increase in right-side endocarditis in drug abusers; might the disruptions caused by crimping increase the risk for prosthetic valve endocarditis in those who have undergone transcatheter valve implantation [19]? Or might these crimpinginduced defects result in valve thrombosis, as it has been previously proposed that early valve thrombosis can result from leaflet disruption [7]? Finally, valve function may be impaired as glutaraldehyde-fixed xenograft tissue has a great deal of elasticity and pliability, and the damage induced by crimping may take away some of this, impairing leaflet function.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worrying that the fact of needing valve leaflets by balloon compression and expansion can theoretically cause premature structural deterioration thereof. [18] In our series, there was no deterioration of leaflets valve function during follow-up.…”
Section: Discussionmentioning
confidence: 40%
“…Furthermore, there are few recent quantitative data that evaluates leaflets in-jury due to crimping. 1,3,20,24,49,93 It has been shown that mechanical stresses affecting pericardial leaflets can cause disruption of collagen fiber orientation, 1 that may lead to calcification and possible early valve failure. 49,74,93 What effects this damage may have on the durability of transcatheter valves compared to surgical bioprosthetic valves is not yet known.…”
Section: Limitations and Challengesmentioning
confidence: 99%